Sosialisasi Penyebab Keterlambatan dan Kendala dalam Proses Pengiriman Barang pada PT. XYZ Cargo Indonesia: Upaya Peningkatan Efisiensi Layanan Logistik - Situmorang, Ben Ony Hottua; Susanto, Primadi Candra; Olfebric, Olfebric; Baskoro, Dian Anom; Simarmata, Juliater (Jurnal Abdimas Transportasi & Logistik, 2024)
This community service activity was conducted as part of an academic initiative to support improvements in logistics service efficiency at PT. XYZ Cargo Indonesia. The background of this activity stems from recurring issues of delivery delays and operational obstacles that negatively impact customer satisfaction and supply chain performance. The purpose of the activity was to raise awareness and enhance the competence of logistics staff in identifying the root causes of shipment delays and implementing effective solutions. The program was carried out through an online socialization session using an interactive approach involving presentations, discussions, and case studies based on real operational situations. The results showed that participants gained a clearer understanding of key delay factors such as poor coordination, documentation errors, and infrastructure limitations. Post-activity evaluations indicated a significant improvement in participants’ ability to plan preventive measures and optimize delivery schedules. In conclusion, this activity successfully contributed to developing a more efficient and responsive logistics management culture at PT. XYZ Cargo Indonesia.